Comparative Genomics Reveals High Genomic Diversity in the Genus Photobacterium - Machado, Henrique; Gram, Lone (Frontiers in Microbiology, 2017)
Vibrionaceae is a large marine bacterial family, which can constitute up to 50% of the prokaryotic population in marine waters. Photobacterium is the second largest genus in the family and we used comparative genomics on 35 strains representing 16 of the 28 species described so far, to understand the genomic diversity present in the Photobacterium genus. Such understanding is important when determining the ecophysiology of the genus. We used whole genome sequences to evaluate phylogenetic relationships using several analyses (16S rRNA, MLSA, fur, amino-acid usage, ANI), which allowed us to identify two misidentified strains. Genome analyses also revealed occurrence of higher and lower GC content clades, correlating with phylogenetic clusters. Pan- and core-genome analysis revealed the conservation of 25% of the genome throughout the genus, with a large and open pan-genome. The major source of genomic diversity could be traced to the smaller chromosome and plasmids. Several of the physiological traits studied in the genus did not correlate with phylogenetic data. Since horizontal gene transfer (HGT) is often suggested as a source of genetic diversity and a driver of genomic evolution in environmental bacterial species, we looked into evidence of such in Photobacterium genomes. Genomic islands were the source of differences in strains of the same species, while number of transposase genes and CRISPR arrays suggested several encounters with foreign DNA. Presence of genomic exchange traits was widespread and abundant in the genus, suggesting a role in genomic evolution and niche adaptation. The high genetic variability and means of genetic exchange make it difficult to conclude on genome evolutionary paths and raise the awareness of the roles of foreign DNA in the genomic evolution of environmental organisms.